Radiopacity of premixed and two-component Calcium silicate-based Root Canal sealers - Dželetović Bojan; Milanović Ivana; Antonijević Đorđe; Badnjar Jovan; Petrov Zoran; Antić Svetlana; Ležaja-Zebić Maja (Balkan Stomatological Society, 2022)
Background/Aim: Radiopacity enables radiographic visualization, which is significant in diagnostic procedures and assessment of the quality of endodontic filling. It is important to compare newly developed endodontic sealers with materials that are already in clinical use in order to promote evidence-based dentistry. The aim of our study was to evaluate radiopacity of different calcium silicate-based sealers in comparison with control, epoxy resin-based sealer. The null hypothesis was that there were no statistically significant differences in radiopacity of the tested sealers. Material and Methods: Premixed (TotalFill BC Sealer, EndoSequence BC Sealer, Ceraseal, Bio-C Sealer), two-component (BioRoot RCS, MTA Fillapex, Bioceramic Root Canal Sealer, GuttaFlow Bioseal) calcium silicate-based sealers and AH Plus, as a control, were used. Specimens were radiographed using a Radiovisiography (RVG-4) CCD (charge-coupled devices)-based digital sensor. Results: Ceraseal had the highest, while Bioceramic Root Canal Sealer had the lowest radiopacity. Bioceramic Root Canal Sealer and MTA Fillapex had radiopacity significantly lower than all other sealers. Radiopacity level of AH Plus, was similar to premixed and significantly higher than radiopacities of all two-component endodontic sealers. Conclusions: Calcium silicate-based sealers radiopacity ranged from slightly above minimal required value (3mm), to a value higher than control sealer. Premixed endodontic sealers showed similar radiopacity as AH Plus which suggests that their clinical performance, in terms of visibility on dental radiograms, should be similar